2014
DOI: 10.1021/nl502372x
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of Carbon Nanodots: Dipole Emission Centers and Electron–Phonon Coupling

Abstract: Inorganic carbon nanomaterials, also called carbon nanodots, exhibit a strong photoluminescence with unusual properties and, thus, have been the focus of intense research. Nonetheless, the origin of their photoluminescence is still unclear and the subject of scientific debates. Here, we present a single particle comprehensive study of carbon nanodot photoluminescence, which combines emission and lifetime spectroscopy, defocused emission dipole imaging, azimuthally polarized excitation dipole scanning, nanocavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
256
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 191 publications
(293 citation statements)
references
References 43 publications
32
256
4
1
Order By: Relevance
“…9, which show that CDs are introduced successfully onto the surface of PPy nanospheres due to the p-p interaction between the PPy and the sp 2 p clouds of CDs (Li et al 2013). The CDs with a size of 3-5 nm present a lattice structure with the lattice spacing of 0.26 nm, which corresponds to the (100) crystal plane of graphite (Ghosh et al 2014).…”
Section: Resultsmentioning
confidence: 89%
“…9, which show that CDs are introduced successfully onto the surface of PPy nanospheres due to the p-p interaction between the PPy and the sp 2 p clouds of CDs (Li et al 2013). The CDs with a size of 3-5 nm present a lattice structure with the lattice spacing of 0.26 nm, which corresponds to the (100) crystal plane of graphite (Ghosh et al 2014).…”
Section: Resultsmentioning
confidence: 89%
“…[21][22][23] Whatever the synthesis route,t he sizes of CNDs typically range from 1-10 nm with different numbers of stacked graphene layers that are saturated with functional groups at their periphery.I mportantly,t heir facile synthesis and low cost make CNDs promising replacements for expensive organic dyes in optoelectronic applications. [21,[24][25][26][27][28] Thec harge-transfer activity of CNDs has recently been explored, both in ground and excited states, [27,29] for the excited states this was done in conjunction with av ariety of electron donors and acceptors. [26,30] Fori nstance,C NDs have been used together with complementary forms of nanocarbons,s uch as fullerenes,c arbon nanotubes,g raphene,i n tailored charge-transfer systems.Inaleading example,CNDs have been combined with single-walled carbon nanotubes (SWCNTs) affording supramolecular nanohybrids,i nw hich the components function as electron donors and acceptors.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that such trap states in the bandgap play an important role for the photoluminescence of CNDs, 16,25,26 and that the trapping effect consists of energy transfer between p-conjugated subdomains within single particles or with the recombination of photogenerated charges at defect centers. 27,28 We found that the fluorescence intensity of CND1 is significantly quenched under acidic conditions (pH 1). Similarly, the absorption in the visible region is reduced - Fig.…”
Section: Conceptual Insightsmentioning
confidence: 84%